Analisis Kesesuaian Lahan untuk Padi di Distrik Semangga, Kabupaten Merauke - ARDIANSYAH ARDIANSYAH; SIDHARTA SAHIRMAN; M. RIF'AN; EDY H.P. MELMAMBESSY (P4W LPPM IPB, 2017)
This study aimed to determine the land suitability for paddy plantation in Semangga subdistrict, Merauke Regency, Papua Province and to identify any treatments that needs to be taken to promote the land suitability classes. The information on land suitability is important to determine the treatment required in land preparation in order to achieve optimal production. Survey was conducted to collect necessary data which includes climate data, nutrient content (N, P, K available), Cation Exchange Capacity (CEC), pH, and toxicity. These data are interpolated within the area of Semangga subdistrict and classified based on the criteria developed by Indonesian Soil Research Institute - Ministry of Agriculture and FAO. Overlay analysis is performed in order to determine land suitability classes and the dominant limiting factor. Criteria for determining the suitability classes was taken from the lowest class of land unit. The results showed that the area of 1% (360.09 hectare) is classified as class of S2wfn, 55.8% (19,495.83 hectare) as class of S3n, 7% (2,431.83 hectare) as class of S3np, 35.3% (12,349.74 hectare) as class N1n, and 0.9% (306.6 hectare) as class of N2f. The finding of land suitability classes and its dominant inhibitory factor can be used then to determine the proper land treatment planning such as fertilization, liming, and drainage system design.